THE REGULATION OF PINOCYTOSIS IN MOUSE MACROPHAGES : I. METABOLIC REQUIREMENTS AS DEFINED BY THE USE OF INHIBITORS - Cohn, Zanvil A. (The Rockefeller University Press, 1966)
A method is described to study the formation of pinocytic vesicles in cultivated mouse macrophages. Vesicles which arise in the peripheral cytoplasm and are in transit to the centrosphere region are enumerated by the phase-contrast microscopy of glutaraldehyde-fixed cells. Under these conditions there is a prompt reversible response of vesicle formation to calf serum factors in the external environment. The reduction of pinosome formation by a variety of metabolic inhibitors was then studied in a medium containing 50% newborn calf serum. Inhibitors of both glycolysis and respiration reduced vesicle formation to low levels. This influence was most striking with cyanide, antimycin A, and anaerobiosis. This indicates an important contribution of an intact respiratory pathway in pinocytosis. Both 2,4-dinitrophenol and oligomycin inhibited vesicle formation at low concentrations. These data suggest a central role of ATP as an energy source for vesicle formation. Inhibitors of protein synthesis, such as puromycin and p-fluorophenylalanine, produced a prompt reduction in vesicle formation. The action of p-fluorophenylalanine was effectively reversed with L-phenylalanine. Actinomycin D depressed pinocytosis to low levels at concentrations of 0.1 to 0.003 µg/ml. This effect was observed only after a 120 min lag phase. A 10°C reduction in ambient temperature lowered vesicle counts to 30% of control preparations at 37°C.